Effect of coronavirus disease 2019 on febrile children’s visits to the emergency department of a tertiary hospital - Jin Ah Kim; Meong Hi Son; Miran Park (Pediatric Emergency Medicine Journal, 2021)
Purpose During the coronavirus disease 2019 pandemic, many countries have reported sharp drops in the numbers of patients, especially children, seeking emergency care unrelated to the disease. The author investigated the patterns of febrile children’s visits to the emergency department (ED) of a tertiary hospital from 2017 through 2020. Methods We compared the data of febrile children aged 15 years or younger who visited the ED in 2017-2019 and in 2020 (February through August, each year). Information on the children’s baseline characteristics, the Korean Triage and Acuity Scale 1-2 indicating a high severity, and ED disposition, such as hospitalization, were collected. In addition, we determined the number of children who underwent cancellation, defined as the leave of children without treatment, and the rates of respiratory virus polymerase chain reaction performance and its positivity. Results In 2020, we noted decreases in the median monthly fever-related ED visits (2017-2019, 326 [interquartile range, 292-425] vs. 2020, 149 [132-182]; P < 0.001) with a shorter median fever duration (2017-2019, 11 [3-27] days vs. 2020, 9 [2-23] days; P < 0.001). However, in the same year, we noted increases in rates of the Korean Triage and Acuity Scale 1-2 (2017-2019, 5.7% vs. 2020, 16.4%; P < 0.001) and hospitalization (2017-2019, 23.5% vs. 2020, 35.7%; P < 0.001). We also noted increases in the number of cancellation and the rate of respiratory virus polymerase chain reaction performance rate, along with a decrease in its positive rate in 2020. Conclusion During the pandemic, the febrile children’s visits to the ED decreased in number. However, the severity remarkably increased, requiring more medical attention.